Studies on the essential oils of Curcuma haritha Mangaly & Sabu and C. raktakanta Mangaly & Sabu - Pushpangadan, Mathew Dan, V George, P (Journal of Spices and Aromatic Crops, 2002)
The essential oils obtained by hydrodistillation from the fresh rhizomes of two endemic species of Curcuma viz. C. haritha and C. raktakanta were studied by GLC analysis. Eleven components were identified from C. haritha of which camphor (21.24%) was the major component and ten components were identified from C. raktakanta of which ethyl p-methoxycinnamate (16.57%) was the major component. a-pinene, b-pinene, camphor, terpinyl acetate, turmerone and ethyl p-methoxycinnamate were common to both species.